Feasibility of MRI to assess differences in ophthalmic artery blood flow rate in normal tension glaucoma and healthy controls. Issue 5 (19th November 2020) - Kristiansen, Martin; Lindén, Christina; Qvarlander, Sara; Wåhlin, Anders; Ambarki, Khalid; Hallberg, Per; Eklund, Anders; Jóhannesson, Gauti
Abstract: Purpose: To examine feasibility of phase‐contrast magnetic resonance imaging (PCMRI) and to assess blood flow rate in the ophthalmic artery (OA) in patients with normal tension glaucoma (NTG) compared with healthy controls. Methods: Sixteen patients with treated NTG and 16 age‐ and sex‐matched healthy controls underwent PCMRI using a 3‐Tesla scanner and ophthalmological examinations. OA blood flow rate was measured using a 2D PCMRI sequence with a spatial resolution of 0.35 mm 2 . Results: The blood flow rate in the NTG group was 9.6 ± 3.9 ml/min [mean ± SD] compared with 11.9 ± 4.8 ml/min in the control group. Resistance Index (RI) and Pulsatility Index (PI) were 0.73 ± 0.08 and 1.36 ± 0.29, respectively, in the NTG group and 0.68 ± 0.13 and 1.22 ± 0.40, respectively, in the healthy group. The mean visual field index (VFI) was 46% ± 25 for the worse NTG eyes. The measured differences observed between the NTG group and the control group in blood flow rate (p = 0.12), RI (p = 0.18) and PI (p = 0.27) were non‐significant. Conclusions: This case–control study, using PCMRI, showed a slight, but non‐significant, reduction in OA blood flow rate in the NTG patients compared with the healthy controls. These results indicate that blood flow may be of importance in the pathogenesis of NTG. Considering that only a limited portion of the total OA blood flow supplies the ocular system and the large inter‐individual differences, a larger study or more advanced PCMRI technique might give the answer.